Birnessite / fulvic acid composite adsorbent and preparation method and application thereof
By adding fulvic acid during the formation of water sodium-manganese ore, the effluent sodium-manganese ore/fulvic acid composite adsorbent is prepared, which solves the problem of easy agglomeration and poor stability of water sodium-manganese nanoparticles, and achieves the adsorption effect of heavy metal ions with high specific surface area, multiple adsorption sites and good stability.
Patent Information
- Application Number
- CN202310345337.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-31
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2043-03-31
AI Technical Summary
Existing sodium-manganese ore nanoparticles are prone to agglomeration and have poor stability, resulting in small specific surface area, limited reactivity, and poor stability of composite adsorbents are prone to secondary pollution.
The effluent sodium-manganese ore/fulligic acid composite adsorbent is prepared by synchronously adding fulligic acid during the formation of sodium-manganese ore, and the co-precipitation reaction is used to uniformly disperse the fulligic acid and load it on the surface, pores and flakes of sodium-manganese ore.
The specific surface area and adsorption capacity of the adsorbent are improved, the adsorption amount of heavy metal ions is enhanced, and the stability and service life of the adsorbent is improved, achieving a low-cost, green and environmentally friendly heavy metal ions adsorption effect.
Smart Images

Figure CN116422296B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of heavy metal pollution prevention and control, relates to a heavy metal adsorption material, specifically to a birnessite / fulvic acid composite adsorbent and a preparation method thereof, and also to an application of the birnessite / fulvic acid composite adsorbent in adsorbing heavy metal ions in a solution system. Background Art
[0002] Heavy metals entering water bodies will cause great harm to the environment and humans. For example, the large amount of high-concentration cadmium-containing wastewater discharged during cadmium industrial mining, mineral processing and smelting is the main source of cadmium pollutants, which will also cause pollution of drinking water, soil, etc. 70% of the world's rivers / lakes are suffering from varying degrees of cadmium pollution. Trace amounts (0.01-0.001 mg / L) of heavy metal cadmium in natural water bodies can produce toxic effects and cause great harm to human organs, especially the kidneys. Therefore, how to make heavy metal-containing wastewater meet standards before discharge is an urgent scientific task.
[0003] At present, the main technologies for treating heavy metal wastewater include chemical coagulation and precipitation, electrochemical precipitation, ion exchange, membrane treatment technology, adsorption method, etc. Among them, adsorption method is one of the most commonly used technologies for treating heavy metal pollution in water bodies. Therefore, finding efficient, cheap and environmentally friendly adsorption materials has also become a research hotspot. Birnessite has weak crystal form and fine particles. It often has the advantages of low zero charge, high cation exchange capacity and strong oxidation ability. Therefore, it plays an important role in the adsorption, desorption and redox process of heavy metals in water and soil. However, the birnessite nanoparticles prepared at present have the disadvantages of easy agglomeration and poor stability in aqueous solution, which will reduce its specific surface area and limit its reaction activity. In recent years, there have been a lot of studies on the preparation of adsorbents by combining metal oxides with birnessite, but these adsorbents are mainly compounded by adsorption reaction. The metal oxides on the surface of the adsorbent obtained are poorly stable and easy to desorb and cause secondary pollution. Therefore, obtaining a birnessite-based composite adsorbent with large specific surface area, multiple adsorption sites, large adsorption capacity, good stability and green environmental protection has important practical significance for the effective treatment of heavy metal wastewater. Summary of the invention
[0004] The technical problem to be solved by the present invention is to overcome the deficiencies of the prior art and provide a birnessite / fulvic acid composite adsorbent having a large specific surface area, multiple adsorption sites, a large adsorption capacity, good stability, and being green and environmentally friendly, as well as a preparation method and application thereof.
[0005] In order to solve the above technical problems, the technical solution adopted by the present invention is:
[0006] A method for preparing a birnessite / fulvic acid composite adsorbent comprises the following steps:
[0007] S1, mixing potassium permanganate, sodium salt and water to obtain mixed solution 1; mixing manganese chloride, fulvic acid and water to obtain mixed solution 2;
[0008] S2. Mixing the mixed solution 1 with the mixed solution 2, stirring, and obtaining a birnessite / fulvic acid composite adsorbent.
[0009] The preparation method of the above-mentioned birnessite / fulvic acid composite adsorbent is further improved. In step S1, the concentration of potassium permanganate in the mixed solution 1 is 0.02mol / L~0.5mol / L; the concentration of sodium salt in the mixed solution 1 is 0.03mol / L~0.15mol / L; the sodium salt is sodium hydroxide; the concentration of manganese chloride in the mixed solution 2 is 0.02mol / L~0.5mol / L; the concentration of fulvic acid in the mixed solution 2 is 3g / L~9.5g / L.
[0010] The preparation method of the above-mentioned birnessite / fulvic acid composite adsorbent is further improved. In step S2, the mixed solution 2 is added to the mixed solution 1, and the addition rate of the mixed solution 2 is 1.5mL / min~2mL / min; the volume ratio of the mixed solution 2 to the mixed solution 1 is 1:1.9~2.1; and the stirring time is 18h~24h.
[0011] The above-mentioned method for preparing the birnessite / fulvic acid composite adsorbent is further improved, in which in step S2, the addition rate of the mixed solution 2 is 1.67 mL / min; the volume ratio of the mixed solution 2 to the mixed solution 1 is 1:2; and the stirring time is 22 h.
[0012] The above-mentioned preparation method of birnessite / fulvic acid composite adsorbent is further improved, in step S2, after the stirring is completed, it also includes the following treatment: centrifuging, washing, drying, grinding, and screening the product obtained after stirring; the washing is to wash the precipitate obtained by centrifugation with deionized water as the washing liquid until the conductivity of the washing liquid is less than 10μS·cm -1 ; The sieve hole size of the sieve is 80 mesh.
[0013] As a general technical concept, the present invention also provides a birnessite / fulvic acid composite adsorbent, comprising birnessite and fulvic acid; the fulvic acid is loaded on the surface, pores and sheets of the birnessite; the mass content of fulvic acid in the birnessite / fulvic acid composite adsorbent is 2% to 20%.
[0014] The above-mentioned birnessite / fulvic acid composite adsorbent is further improved and is prepared by the above-mentioned preparation method.
[0015] As a general technical concept, the present invention also provides a use of the above-mentioned birnessite / fulvic acid composite adsorbent in treating heavy metal wastewater.
[0016] The above application is further improved, and the application includes the following steps: mixing the birnessite / fulvic acid composite adsorbent with heavy metal wastewater, stirring, and completing the treatment of heavy metals in the wastewater; the mass volume ratio of the birnessite / fulvic acid composite adsorbent to the heavy metal wastewater is 0.1g:300mL.
[0017] The above application is further improved, the heavy metal ion in the heavy metal wastewater is Cd 2+ ; The initial concentration of heavy metal ions in the heavy metal wastewater is ≤200 mg / L; the pH value of the heavy metal wastewater is 6; the stirring time is 24 hours.
[0018] Compared with the prior art, the advantages of the present invention are:
[0019] (1) In view of the defects of the existing birnessite such as easy agglomeration and stability, as well as the defects of the birnessite-based composite adsorbent such as poor stability and easy secondary pollution, the present invention creatively proposes a method for preparing a birnessite / fulvic acid composite adsorbent, wherein fulvic acid is simultaneously added during the formation of birnessite, so that the fulvic acid can be uniformly dispersed and loaded on the surface of the birnessite, as well as loaded in the pores and sheets of the birnessite by a coprecipitation reaction, wherein the fulvic acid is uniformly dispersed on the surface of the birnessite, which is beneficial to not only improving the dispersibility of the birnessite nanoparticles, but also beneficial to In order to improve the specific surface area and adsorption capacity of the adsorbent, and because fulvic acid is a natural organic complex, its surface has a large number of negative charges and metal ion complexing sites, so the fulvic acid is evenly loaded on birnessite, which can provide a large number of heavy metal ion adsorption sites, and is also conducive to improving the adsorption of heavy metal ions by the adsorbent. At the same time, the fulvic acid is loaded in the pores and sheets of birnessite, so that the stability of fulvic acid in the water environment is better, which is conducive to improving the service life of the adsorbent, and can be used for adsorption of heavy metal ions in wastewater for many times and for a long time, and the economic benefit is better. In addition, compared with metal oxides, the fulvic acid used in the present invention is a biomass material, which is safer and cheaper, and is thus conducive to obtaining low-cost, green and environmentally friendly adsorption materials. The birnessite / fulvic acid composite adsorbent prepared in the present invention has the advantages of large specific surface area, multiple adsorption sites, large adsorption capacity, good stability, green environmental protection, etc. It is a new heavy metal ion adsorbent with low cost and excellent performance, which can be widely used for adsorbing heavy metal ions in water bodies, and has good adsorption effect and high adsorption efficiency. It has high use value and good application prospects, and has very important practical significance for achieving effective treatment of heavy metal polluted wastewater. At the same time, the preparation method of the present invention also has the advantages of simple process, controllable process, continuous production, etc., is suitable for large-scale preparation, and is convenient for industrial application.
[0020] (2) In the preparation method of the present invention, the mixed solution 2 containing fulvic acid is added to the mixed solution 1 containing potassium permanganate. The addition rate of the mixed solution 2 containing fulvic acid is optimized to 1.5 mL / min to 2 mL / min, especially to 1.67 mL / min, which is conducive to forming more dispersed composite particles, so that the specific surface area of the material is larger and the adsorption performance is better. At the same time, the stirring time of the mixed solution containing potassium permanganate, sodium salt, manganese chloride and fulvic acid is also optimized to 18 h to 24 h. By optimizing the stirring time to 18 h to 24 h, especially to 22 h, the coprecipitation reaction reaches equilibrium, and the fulvic acid is evenly dispersed and loaded on the surface of birnessite, as well as loaded in the pores and sheets of birnessite. This is because if the stirring time is too short, the reaction is insufficient and the quality of the generated product is small, while if the stirring time is too long, the mineral structure is easily transformed and deteriorated, which is not conducive to improving the adsorption performance.
[0021] (3) The birnessite / fulvic acid composite adsorbent of the present invention comprises birnessite and fulvic acid, wherein the fulvic acid is loaded on the surface, pores and sheets of the birnessite, wherein the mass content of fulvic acid in the birnessite / fulvic acid composite adsorbent is 2% to 20%. In the present invention, by optimizing the content of fulvic acid, the adsorption performance of the adsorbent can be further improved under the premise of ensuring that the birnessite nanoparticles have good dispersibility, because when the content of fulvic acid in the adsorbent is low (such as less than 2%), less fulvic acid is not conducive to effectively improving the dispersibility of the birnessite nanoparticles, so that the adsorbent still has defects such as easy agglomeration and small specific surface area, and when the content of fulvic acid in the adsorbent is high (such as higher than 20%), too much fulvic acid will block the pores of the birnessite, which is not only not conducive to improving the adsorption capacity of the adsorbent, but also will increase the cost, and bring the risk of secondary pollution due to the reduction of divalent manganese.
[0022] (4) The present invention also provides an application of a birnessite / fulvic acid composite adsorbent in treating heavy metal wastewater. Taking heavy metal cadmium wastewater as an example, by mixing the birnessite / fulvic acid composite adsorbent with the heavy metal cadmium wastewater and stirring, the heavy metal cadmium in the wastewater can be quickly and thoroughly removed. The invention has the advantages of convenient operation, high treatment efficiency, good removal effect, etc., and is of great significance for effectively removing heavy metals in water bodies. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to make the purpose, technical solution and advantages of the embodiments of the present invention more clear, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the accompanying drawings in the embodiments of the present invention.
[0024] Figure 1 This is a TEM image of the birnessite / fulvic acid composite adsorbent prepared in Example 1 of the present invention.
[0025] Figure 2 1 is the XRD diagram of the birnessite / fulvic acid composite adsorbent prepared in Examples 1 and 3 of the present invention.
[0026] Figure 3 This is the isotherm diagram of the adsorption of CdCⅡC by the birnessite / fulvic acid composite adsorbent (5wt% fulvic acid / birnessite, 15wt% fulvic acid / birnessite) in Example 4 of the present invention. DETAILED DESCRIPTION
[0027] The present invention is further described below in conjunction with the accompanying drawings and specific preferred embodiments, but the protection scope of the present invention is not limited thereby.
[0028] In the following examples, unless otherwise specified, the materials and instruments used are commercially available, the processes used are conventional processes, the equipment used are conventional equipment, and the data obtained are the average values of more than three repeated experiments.
[0029] Example 1
[0030] A method for preparing a birnessite / fulvic acid composite adsorbent comprises the following steps:
[0031] (1) 6.292 g of manganese chloride was added to 300 mL of deionized water and mixed evenly, and then 0.922 g of fulvic acid was added and mixed evenly to obtain a mixed solution of manganese chloride and fulvic acid.
[0032] (2) adding 1.58 g of potassium permanganate to 200 mL of deionized water to obtain a 50 mmol / L potassium permanganate solution; adding 0.8 g of sodium hydroxide to 400 mL of deionized water to obtain a 50 mmol / L sodium hydroxide solution; and uniformly mixing the obtained potassium permanganate solution and the sodium hydroxide solution to obtain a mixed solution of potassium permanganate and sodium hydroxide.
[0033] (3) adding the mixed solution of manganese chloride and fulvic acid prepared in step (1) to the mixed solution of potassium permanganate and sodium hydroxide prepared in step (2) by a constant flow pump, the flow rate of the constant flow pump is 1.67 mL / min, the reaction time is 3 hours, and the magnetic stirring is continued for 18 hours, the precipitate is centrifuged, and the precipitate is washed with deionized water until the conductivity of the supernatant is less than 10 μS·cm -1 , freeze-dried, ground into powder, and sieved (the sieve size is 80 mesh) to obtain a birnessite / fulvic acid composite adsorbent, recorded as 5wt% fulvic acid / birnessite.
[0034] The birnessite / fulvic acid composite adsorbent prepared in this embodiment includes birnessite and fulvic acid, and the fulvic acid is loaded on the surface, pores and sheets of the birnessite, wherein the mass content of fulvic acid in the birnessite / fulvic acid composite adsorbent is 5%.
[0035] Figure 1 TEM image of the birnessite / fulvic acid composite adsorbent prepared in Example 1 of the present invention. Figure 1 As shown, the birnessite / fulvic acid composite adsorbent is petal-shaped, and the dispersibility of the adsorbent is significantly improved after being loaded with fulvic acid.
[0036] In addition, after testing, by loading fulvic acid, the specific surface area of the birnessite / fulvic acid composite adsorbent of the present invention increased from 161.32 m 2 / g increased to 254.77m 2 / g.
[0037] Example 2
[0038] A method for preparing a birnessite / fulvic acid composite adsorbent comprises the following steps:
[0039] (1) 6.292 g of manganese chloride was added to 300 mL of deionized water and mixed evenly, and then 1.84 g of fulvic acid was added and mixed evenly to obtain a mixed solution of manganese chloride and fulvic acid.
[0040] (2) adding 1.58 g of potassium permanganate to 200 mL of deionized water to obtain a 50 mmol / L potassium permanganate solution; adding 0.8 g of sodium hydroxide to 400 mL of deionized water to obtain a 50 mmol / L sodium hydroxide solution; and uniformly mixing the obtained potassium permanganate solution and the sodium hydroxide solution to obtain a mixed solution of potassium permanganate and sodium hydroxide.
[0041] (3) adding the mixed solution of manganese chloride and fulvic acid prepared in step (1) to the mixed solution of potassium permanganate and sodium hydroxide prepared in step (2) by a constant flow pump, the flow rate of the constant flow pump is 1.67 mL / min, the reaction time is 3 hours, and the magnetic stirring is continued for 18 hours, and the precipitate is centrifuged and washed with deionized water until the conductivity of the supernatant is less than 10 μS·cm -1 , freeze-dried, ground into powder, and sieved (the sieve size is 80 mesh) to obtain birnessite / fulvic acid composite adsorbent.
[0042] The birnessite / fulvic acid composite adsorbent prepared in this embodiment includes birnessite and fulvic acid, and the fulvic acid is loaded on the surface, pores and sheets of the birnessite, wherein the mass content of fulvic acid in the birnessite / fulvic acid composite adsorbent is 10%.
[0043] In addition, after testing, by loading fulvic acid, the specific surface area of the birnessite / fulvic acid composite adsorbent of the present invention increased from 161.32 m 2 / g increased to 236.37m 2 / g.
[0044] Example 3
[0045] A method for preparing a birnessite / fulvic acid composite adsorbent for efficiently treating cadmium-containing wastewater comprises the following steps:
[0046] (1) 6.292 g of manganese chloride was added to 300 mL of deionized water and mixed evenly, and then 2.75 g of fulvic acid was added and mixed evenly to obtain a mixed solution of manganese chloride and fulvic acid.
[0047] (2) adding 1.58 g of potassium permanganate to 200 mL of deionized water to obtain a 50 mmol / L potassium permanganate solution; adding 0.8 g of sodium hydroxide to 400 mL of deionized water to obtain a 50 mmol / L sodium hydroxide solution; and uniformly mixing the obtained potassium permanganate solution and the sodium hydroxide solution to obtain a mixed solution of potassium permanganate and sodium hydroxide.
[0048] (3) adding the mixed solution of manganese chloride and fulvic acid prepared in step (1) to the mixed solution of potassium permanganate and sodium hydroxide prepared in step (2) by a constant flow pump, the flow rate of the constant flow pump is 1.67 mL / min, the reaction time is 3 hours, and the magnetic stirring is continued for 18 hours, and the precipitate is centrifuged and washed with deionized water until the conductivity of the supernatant is less than 10 μS·cm -1 , freeze-dried, ground into powder, and sieved (the sieve size is 80 mesh) to obtain a birnessite / fulvic acid composite adsorbent, recorded as 15wt% fulvic acid / birnessite.
[0049] The birnessite / fulvic acid composite adsorbent prepared in this embodiment includes birnessite and fulvic acid, and the fulvic acid is loaded on the surface, pores and sheets of the birnessite, wherein the mass content of fulvic acid in the birnessite / fulvic acid composite adsorbent is 15%.
[0050] Figure 2 : is the XRD pattern of the birnessite / fulvic acid composite adsorbent prepared in Examples 1 and 3 of the present invention. Figure 2 As shown, the XRD spectrum of the birnessite / fulvic acid composite adsorbent prepared by the present invention is basically consistent with that of the birnessite without fulvic acid loading.
[0051] In addition, after testing, by loading fulvic acid, the specific surface area of the birnessite / fulvic acid composite adsorbent of the present invention increased from 161.32 m 2 / g increased to 219.10m 2 / g.
[0052] Example 4
[0053] Application of a birnessite / fulvic acid composite adsorbent in treating heavy metal wastewater, specifically using the birnessite / fulvic acid composite adsorbent in Example 1 and Example 3 to treat heavy metal cadmium wastewater
[0054] 0.1 g of the birnessite / fulvic acid composite adsorbent prepared in Example 1 and Example 3 was added to 300 mL of heavy metal cadmium wastewater with a CdCⅡC concentration of 200 mg / L (the initial pH value of the wastewater was 6.0), and stirred for 24 hours to complete the treatment of heavy metal cadmium in the wastewater.
[0055] After the treatment is completed, the supernatant is filtered to obtain the supernatant, and the residual content of CdCⅡC is measured by inductively coupled plasma spectrometer (ICP). The amount of CdCⅡC adsorbed by the adsorbent is calculated by conversion.
[0056] The results show that:
[0057] The adsorption capacity of CdCⅡC by birnessite / fulvic acid composite adsorbent (5wt% fulvic acid / birnessite) is 112.09 mg / g.
[0058] The adsorption capacity of CdCⅡC by birnessite / fulvic acid composite adsorbent (15wt% fulvic acid / birnessite) is 136.83mg / g.
[0059] In addition, in this example, the adsorption effect of birnessite / fulvic acid composite adsorbent (5wt% fulvic acid / birnessite, 15wt% fulvic acid / birnessite) on wastewater with different concentrations of heavy metal cadmium was also investigated. The results are as follows: Figure 3 shown.
[0060] Figure 3 The isotherm diagram of the adsorption of CdCⅡC by the birnessite / fulvic acid composite adsorbent (5wt% fulvic acid / birnessite, 15wt% fulvic acid / birnessite) in Example 4 of the present invention. Figure 3 It can be seen that the equilibrium adsorption amount of CdCⅡC by the adsorbent is q e As the equilibrium concentration C e increases with the increase of C e When it increases to a certain extent, q e The basic stability reaches equilibrium. The reason is that at low CdCⅡC concentrations, the adsorbent has more and more functional groups, which increases the adsorption of CdCⅡC by the material. As the initial concentration of CdCⅡC continues to increase, the adsorption sites of the adsorbent gradually reach saturation, and finally the adsorption of CdCⅡC reaches equilibrium. The saturated adsorption of CdCⅡC by 5wt% fulvic acid / birnessite and 15wt% fulvic acid / birnessite are 112.09mg / g and 136.83mg / g, respectively. Compared with existing reports, their adsorption capacity is higher than other types of manganese oxide composite adsorbents.
[0061] As can be seen from the above results, in the preparation method of the present invention, fulvic acid is added synchronously during the formation of birnessite, so that fulvic acid can be uniformly dispersed and loaded on the surface of birnessite by coprecipitation reaction, and loaded in the pores and sheets of birnessite, and the birnessite / fulvic acid composite adsorbent prepared thereby has the advantages of large specific surface area, many adsorption sites, large adsorption capacity, good stability, green environmental protection, etc., is a new heavy metal ion adsorbent with low cost and excellent performance, can be widely used in adsorbing heavy metal ions in water bodies, and has good adsorption effect and high adsorption efficiency, has very high use value and good application prospects, and has very important practical significance for realizing the effective treatment of heavy metal polluted wastewater. At the same time, the preparation method of the present invention also has the advantages of simple process, controllable process, continuous production, etc., is suitable for large-scale preparation, and is convenient for industrial application.
[0062] The above is only a preferred embodiment of the present invention, but it is not intended to limit the present invention. Any person skilled in the art can make many possible changes and modifications to the technical solution of the present invention using the methods and technical contents disclosed above. Therefore, any simple modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention still falls within the scope of protection of the technical solution of the present invention.
Claims
1. A method for preparing a birnessite / fulvic acid composite adsorbent, characterized in that: The following steps are involved: S1, mixing potassium permanganate, sodium salt and water to obtain a mixed solution 1; mixing manganese chloride, fulvic acid and water to obtain a mixed solution 2; the concentration of fulvic acid in the mixed solution 2 is 3 g / L to 9.5 g / L; S2. Add the mixed solution 2 to the mixed solution 1 at a rate of 1.5 mL / min to 2 mL / min, and stir for 18 h to 24 h to obtain a birnessite / fulvic acid composite adsorbent.
2. The method for preparing the birnessite / fulvic acid composite adsorbent according to claim 1, characterized in that: In step S1, the concentration of potassium permanganate in the mixed solution 1 is 0.02 mol / L to 0.5 mol / L; the concentration of sodium salt in the mixed solution 1 is 0.03 mol / L to 0.15 mol / L; the sodium salt is sodium hydroxide; and the concentration of manganese chloride in the mixed solution 2 is 0.02 mol / L to 0.5 mol / L.
3. The method for preparing the birnessite / fulvic acid composite adsorbent according to claim 1 or 2, characterized in that: In step S2, the volume ratio of the mixed solution 2 to the mixed solution 1 is 1:1.9-2.
1.
4. The method for preparing the birnessite / fulvic acid composite adsorbent according to claim 3, characterized in that: In step S2, the addition rate of the mixed solution 2 is 1.67 mL / min; the volume ratio of the mixed solution 2 to the mixed solution 1 is 1:2; and the stirring time is 22 h.
5. The method for preparing the birnessite / fulvic acid composite adsorbent according to claim 4, characterized in that: In step S2, after the stirring is completed, the following treatment is further included: centrifuging, washing, drying, grinding, and sieving the product obtained after stirring; the washing is to wash the precipitate obtained by centrifugation with deionized water as a washing liquid until the conductivity of the washing liquid is less than 10 μS·cm -1 ; The sieve hole size of the sieve is 80 mesh.
6. A birnessite / fulvic acid composite adsorbent prepared by the preparation method according to any one of claims 1 to 5, characterized in that: It comprises birnessite and fulvic acid; the fulvic acid is loaded on the surface, pores and sheets of the birnessite; and the mass content of fulvic acid in the birnessite / fulvic acid composite adsorbent is 2% to 20%.
7. Use of the birnessite / fulvic acid composite adsorbent as claimed in claim 6 in treating heavy metal wastewater.
8. The use according to claim 7, characterized in that The application comprises the following steps: mixing the birnessite / fulvic acid composite adsorbent with heavy metal wastewater, stirring, and completing the treatment of heavy metals in the wastewater; the mass volume ratio of the birnessite / fulvic acid composite adsorbent to the heavy metal wastewater is 0.1 g: 300 mL.
9. The use according to claim 8, characterized in that: The heavy metal ions in the heavy metal wastewater are Cd 2+ ; The initial concentration of heavy metal ions in the heavy metal wastewater is ≤200 mg / L; the pH value of the heavy metal wastewater is 6; the stirring time is 24 hours.